High expression of LC3A, LC3B, and p62/SQSTM1 autophagic proteins in human colonic ganglion cells - Awi, Noel Jacques *; Armon, Subasri; Peh, Kaik-Boo; Peh, Suat Cheng *; Teow, Sin Yeang * (College of Pathologists, Academy of Medicine Malaysia, 2020)
Introduction: Autophagy is a mechanism that degrades large damaged organelles and misfolded proteins to maintain the homeostasis in all cells. It plays double-faceted roles in tumourigenesis and prevention of various cancers. In our side observation of investigating the prognostic value of autophagy in colorectal cancer (CRC), we found high expression of autophagy proteins (LC3A, LC3B, and p62/SQSTM1) in the colonic ganglion cells. To our best understanding, this is the first paper reporting such finding. Materials and Methods: Formalin-fixed paraffin-embedded (FFPE) CRC tissues blocks were retrieved and confirmed by haematoxylin & eosin (H&E) staining. Immunohistochemistry (IHC) targeting autophagy proteins (LC3A, LC3B, and p62/SQSTM1) was then performed followed by pathological examination. Results: All three autophagy proteins were present in both normal and tumour tissues of CRC patients. Interestingly, high expression of autophagy proteins in colonic ganglion cells was consistently seen regardless of tissue type (normal or cancer) or tumour site (caecum, ascending, transverse, descending, sigmoid colon and rectum). Conclusions: This work highlights the high autophagic activities in human colonic ganglion cells.